2020
DOI: 10.3390/ijms21239043
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Omics Integration Highlights the Role of Ubiquitination in CCl4-Induced Liver Fibrosis

Abstract: Liver fibrosis is the excessive accumulation of extracellular matrix proteins that occurs in chronic liver disease. Ubiquitination is a post-translational modification that is crucial for a plethora of physiological processes. Even though the ubiquitin system has been implicated in several human diseases, the role of ubiquitination in liver fibrosis remains poorly understood. Here, multi-omics approaches were used to address this. Untargeted metabolomics showed that carbon tetrachloride (CCl4)-induced liver fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 47 publications
1
14
0
Order By: Relevance
“…The results revealed that both PCNA and VEGF levels were elevated in the liver tissues of mice injected with CCl 4 compared to normal mice. These outcomes are consistent with the previous published studies ( Huang et al, 2018 , Rahmani et al, 2019 , Mercado-Gómez et al, 2020 ). On the other hand, the increased levels of PCNA and VEGF were normalized after the treatment with the phthalimide analog.…”
Section: Discussionsupporting
confidence: 94%
“…The results revealed that both PCNA and VEGF levels were elevated in the liver tissues of mice injected with CCl 4 compared to normal mice. These outcomes are consistent with the previous published studies ( Huang et al, 2018 , Rahmani et al, 2019 , Mercado-Gómez et al, 2020 ). On the other hand, the increased levels of PCNA and VEGF were normalized after the treatment with the phthalimide analog.…”
Section: Discussionsupporting
confidence: 94%
“…Several factors, such as hypoxia, pathological injury, and cell proliferation via the NOD-like receptor inflammasome pathway, contribute to increased expression of PCNA and CK-7 in the liver [ 38 41 ]. Increased expression of CK-7 and PCNA has been reported in liver transplant patients due to recurrence of liver complications, drug toxicity-induced hypoxia, and liver fibrosis [ 42 44 ]. Increased expression of PCNA and CK-7 in current findings may imply liver injury associated with dysregulation of antioxidants and lipid peroxidation.…”
Section: Discussionmentioning
confidence: 99%
“…TGF-β (Friedmann, 2008). Maintaining quiescence and activation of HSC is a highly dynamic and complex process (Krizhanovsky et al 2008; Kisseleva et al 2012; Mercado-Gómez et al 2020). Accordingly, the progression and regression of liver disease in response to repetitive injuries at the patient’s level are also highly variable (Bedossa et al 2003; Sun et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Using only a single level of measurement, e.g., transcriptomics or histopathology, limits the detection of possible alterations to one type, and thus captures changes only for a small subset of possible components interacting and steering the disease progression (Ogris et al 2021). To obtain a holistic view and reduce the single-level technical effects, studies utilizing multiple omic measurements are employed to support findings or identify targetable molecules in a specific disease context (Mardinoglu et al 2018; Mercado-Gómez et al 2020). Approaches using multi-level analysis outperform single-level analysis, as those are limited in their information content to one level and therefore may lead to missing and misinterpreted results (Domenico et al 2015, Schmitt et al 2013).…”
Section: Introductionmentioning
confidence: 99%